Motion Measurement and Analysis of Different Instruments for Single-Incision Laparoscopic Surgery - Kunyong Lyu; Lixiao Yang; Chengli Song (Applied Bionics and Biomechanics)
Objective. To objectively compare and analyze the range of motion of three types of instruments for single-incision laparoscopic surgery. Material and Methods. Ten experienced participants were recruited. Straight instruments (Group A), straight/articulating instruments (Group B), and precurved instruments (Group C) were used to complete the transferring task through one site in a laparoscopic simulator. Straight instruments via two separate sites (Group D) served as control. The operation time of each group was recorded. Instrument positions were measured by an optical tracking system. The inserted length and pivoting angles were derived via MATLAB. Results. There was a significant difference in operation time between groups (D<A<B<C, p<0.01). The range of motion of instruments was different on instrument types and surgical approaches. A significant difference in the inserted length was found between groups. Instrument conflicts and inadequate triangulation were found in Group A; instrument conflicts were found in Group B; no obvious conflicts and triangulation problems were observed in Group C. The operation in Group C was similar to the operation in Group D but differed on the left/right pivoting angles. Conclusion. Different types of instruments have different ranges of motion in single-incision laparoscopic surgery. Working with precurved instruments seems like a compromise to traditional laparoscopic surgery if the transmission property, and shaft curvature of the instruments could be improved. An integrated mechanical platform or robotic system might be the ultimate solution for single-incision laparoscopic surgery to pursue even less trauma.